Redefining mixed-use buildings integrating vertical farms to multi-storey commercial-residential structures to create sustainable vertical communities in Davao City - Magdadaro, Jahzeel V. (2011)
Davao City population is growing, but its land area is not. This fact, though not alarming at the moment because of Davao City's large area, will be evident in the near future when the population will be expected to double in 24 years. A need to provide these new arrivals with housing areas and sufficient food without spending too much on food transport cost would be more cost efficient. This study which aims to address the future problems of food and land shortage dwells mainly on the integration of vertical farms and commercial areas on multi-storied residential buildings in Davao City to both produce food for and give shelter to residents with the least land footprint in an urban setting. For this building to be feasible, the most efficient floor area ratio of the residential to commercial to farm areas will be calculated. The basis for obtaining the most efficient ratio were: (1) its capacity to supply 75% of the residents with food, and (2) that it should generate a gross profit greater than that of a typical condominium building in Davao City in 5 years. The result of the computations shows that the integration of farm to mixed-use residential-commercial buildings in Davao City is feasible. The most efficient residential: Commercial: Farm floor area ratio was computed to be 50:5:20. this means that 50% of the building's gross floor area should be alloted to residential units, 5% to commercial units, and 20% to farm units. This ratio could sufficiently supply 75% of the residents with food all year round and at the same time, generate greater profit in five years